Slovakia Catching-up Regions : Unlocking the Endogenous Tourism Potential of Poloniny National Park and the Snina District of the Slovak Republic - World Bank Group (World Bank, Washington, DC, 2019)
The report examines the current tourism development and market of the Prešovský Samosprávny Kraj, Presov Self-Governing Region (PSK), focusing particularly on the lagging district of Snina and the National Park of Poloniny, and the opportunities for their improvement as potential drivers of equitable local economic growth in the PSK. It is being conducted in support of the European Commission (EC's) Catching Up Regions Initiative. The PSK location and its unique natural and cultural heritage features make it a tourism-friendly potential destination. The Snina District and National Poloniny Park (NPP) have many challenges to address in order to realize the growth benefits of their tourism sector. This report recommends a set of interrelated actions to create the cohesion needed to stimulate tourism as a major economic driver for the region.